Prevalence of Pseudomonas aeruginosa and Acinetobacter spp. in subgingival biofilm and saliva of subjects with chronic periodontal infection - Souto, Renata (Sociedade Brasileira de Microbiologia, 2014)
P. aeruginosa and Acinetobacter spp. are important pathogens associated with late nosocomial pneumonia in hospitalized and institutionalized individuals. The oral cavity may be a major source of these respiratory pathogens, particularly in the presence of poor oral hygiene and periodontal infection. This study investigated the prevalence of P. aeruginosa and Acinetobacter spp. in subgingival biofilm and saliva of subjects with periodontal disease or health. Samples were obtained from 55 periodontally healthy (PH) and 169 chronic periodontitis (CP) patients. DNA was obtained from the samples and detection of P. aeruginosa and Acinetobacter spp. was carried out by multiplex and nested PCR. P. aeruginosa and Acinetobacter spp. were detected in 40% and 45% of all samples, respectively. No significant differences in the distribution of these microorganisms between men and women, subgingival biofilm and saliva samples, patients ≤ 35 and > 35 years of age, and smokers and non-smokers were observed regardless periodontal status (p > 0.05). In contrast, the frequencies of P. aeruginosa and Acinetobacter spp. in saliva and biofilm samples were significantly greater in CP than PH patients (p < 0.01). Smokers presenting P. aeruginosa and high frequencies of supragingival plaque were more likely to present CP than PH. P. aeruginosa and Acinetobacter spp. are frequently detected in the oral microbiota of CP. Poor oral hygiene, smoking and the presence of P. aeruginosa are strongly associated with periodontitis.